Exploring the perceptions of the effect of the COVID-19 pandemic on the mental well-being and medical education of medical students in Northern Ireland, in addition to the perceived barriers to seeking support; a qualitative study. - Claire Whiteside; Gonnie Klabbers (PLoS ONE)
Introduction The COVID-19 pandemic had a negative effect on population mental health. Medical students may have been particularly affected, whom prevalence of mental health conditions was already high before the pandemic hit, due to the difficult and stressful academic programme. In Northern Ireland specifically, mental well-being levels are the lowest across the UK; however limited research exists examining the medical student cohort. This study explores Northern Irish medical students' perceptions on how the pandemic affected their mental health, their progress within medical education and perceived barriers to accessing support services in Northern Ireland. Methods A qualitative study of phenomenological design involving 15 in-depth semi-structured interviews. The interviews were conducted amongst individuals who were 1st-4th year medical students when the pandemic was officially declared in Northern Ireland in March 2020. The interviews were transcribed, and thematic analysis was carried out using NVivo V12 qualitative data analysis software. Results Results demonstrated the COVID-19 pandemic had a considerable negative impact on participants' mental health; a variety of interlinked social, individual and/or psychological and organisational factors led to increased levels of stress, anxiety and depression. This had a secondary negative impact on participants' medical education progress through reducing motivation, causing burnout and impostor syndrome. Unexpectedly; there were some perceived positive outcomes, including improved appreciation for work-life balance and resilience. Participants reported various barriers to seeking help amongst this difficult time period; also categorizable into social, individual and/or psychological and organisational factors, for example; stigmatisation, fear and perfectionistic tendencies. Discussion and conclusion There is a pressing demand for heightened support availability, personally tailored mental health assistance and an effort to reduce mental health stigma in Northern Ireland. This study highlights the complex multifactorial nature of mental health. Medical schools must provide additional services to protect well-being during particularly challenging periods and dismantle the barriers preventing individuals from accessing vital support.